2019
DOI: 10.3390/ijms20246341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Dissection of Photosynthesis in Barley Exposed to Drought Stress

Abstract: Balanced photosynthesis under drought is essential for better survival and for agricultural benefits in terms of biomass and yield. Given the current attempts to improve the photosynthetic efficiency for greater crop yield, the explanation of the genetic basis of that process, together with the phenotypic analysis, is significant in terms of both basic studies and potential agricultural application. Therefore, the main objective of this study was to uncover the molecular basis of the photosynthesis process und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…Further, the K-band is known to be a very good indicator of various stressful conditions, especially drought (Oukarroum et al 2007, Jedmowski et al 2013, Daszkowska-Golec et al 2019. Six out of ten genotypes revealed positive inflections of the K-band at anthesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, the K-band is known to be a very good indicator of various stressful conditions, especially drought (Oukarroum et al 2007, Jedmowski et al 2013, Daszkowska-Golec et al 2019. Six out of ten genotypes revealed positive inflections of the K-band at anthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, proline synthesis can also be a result of plant developmental stage and higher concentrations of proline can be expected in generative plant parts during flowering (Kavi Kishor et al 2015). In addition, a recent study showed that the positive K-band is also associated with downregulation of genes encoding PsbC, PsbE which play a significant role in attaching PsbO to OEC in response to drought in two barley cultivars (Daszkowska-Golec et al 2019). These results corroborate our findings and suggest impaired electron flow between the OEC and the acceptor side of the PSII RC in six barley genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The J-I (3–30 ms) phase describes a reduction of the plastoquinone (PQ) pool. The I-P (30–200 ms) phase is connected to the final reduction of the electron acceptors of the photosystem I (PSI): PC (plastocyanin), P700 (photosystem I), the Fe/S (iron-sulfur) clusters and Fd (ferredoxin) [ 75 ]. Higher MeJA concentrations induced changes in photosystem designated by occurrence of additional peak—a K-band.…”
Section: Resultsmentioning
confidence: 99%
“…To answer the question whether the sensitivity to drought of hvd14.d was caused by a disturbance in the ABA metabolism, the concentration of ABA and its metabolites was analysed. Recent findings demonstrated that physiological changes evoked by rapid dehydration are similar to that induced by soil drought stress in barley (Daszkowska-Golec et al, 2019)., Therefore we used a rapid dehydration assay which enabled us collecting enough amount of leaf tissue for hormone measurements. Increased levels of ABA are characteristic for plants exposed to drought stress (Ye, Zhu, Liu, Li, & Zhang, 2011).…”
Section: Sensitivity Of Ojip Curve and Parameters Calculated Based Onmentioning
confidence: 99%
“…Photosystem II is more affected by drought in hvd14.d than in SebastianSince photosystem II (PSII) activity and repair is sensitive to drought(Daszkowska-Golec et al, 2019;Gururani, Venkatesh, & Tran, 2015) changes in electron transfer reactions of PSII using the prompt chloro-phyll a fluorescence induction kinetics (OJIP test) were investigated. Both, WT and hvd14.d revealed characteristic OJIP curve shapes under control conditions.…”
mentioning
confidence: 99%